1977
DOI: 10.1111/j.1399-3054.1977.tb09284.x
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid and the Germination of Thermodormant Lettuce Fruits (Lactuca sativa cv. Grand Rapids). The Fate of Isotopically Labelled Abscisic Acid

Abstract: ABA inhibits the germination of Grand Rapids lettuce seeds at a temperature at which photoblastism is not observed. This ABA inhibition can be overcome by GA, or cytokinin, or red light acting alone or in concert. At high levels of ABA the ameliorative effects of GA, cytokinin or red light are not manifest and it is suggested that lettuce seeds' response to a given level of ABA is temperature dependent, and any interaction which may be observed between ABA and other regulators, or red light, likewise is temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The pattern of distribution of radioactivity after TLC in metabolic extracts of lettuce seed cv. Olof (Fig, 5) iooks similar to data obtained by Robertson and Berrie (1977) with seeds of the cultivar Grand Rapids in the same solvent system. As in their study, the exact nature of the metabolites remained obscure, lt could only be excluded that decarboxylation takes a major part in the metabolic conversion of ABA in lettuce seeds (Tab.…”
Section: Metabolism Of Abasupporting
confidence: 75%
“…The pattern of distribution of radioactivity after TLC in metabolic extracts of lettuce seed cv. Olof (Fig, 5) iooks similar to data obtained by Robertson and Berrie (1977) with seeds of the cultivar Grand Rapids in the same solvent system. As in their study, the exact nature of the metabolites remained obscure, lt could only be excluded that decarboxylation takes a major part in the metabolic conversion of ABA in lettuce seeds (Tab.…”
Section: Metabolism Of Abasupporting
confidence: 75%
“…The data presented here also confirm the reversibility of ABA inhibition of lettuce seed germination by GA or light treatments (Poggi-Pellegrin andBulard 1976, Robertson andBerrie 1977). The fact that in both cases ABA applied later than the stimulatory factor caused lower inhibition (higher percentage germination) than when applied before GA, or light, seems to indicate the secondary character of ABA action upon the mechanisms triggered by germination stimulators.…”
Section: Discussionsupporting
confidence: 82%
“…Black 1969, and abscisie aeid inhibits their germination (Reynolds and Thompson 1973). Experiments with Grand Rapids seeds have shown that ABA inhibition can be reversed by GA,, GA4 or light (Poggi-Pellegrin andBulard 1976, Robertson andBerrie 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to ethylene, GA, and red light can increase the upper temperature limit of lettuce seed germination, and exposure to ABA can decrease it (Reynolds and Thompson, 1973;Saini et al, 1986Saini et al, , 1989Dutta and Bradford, 1994;Kristie and Fielding, 1994;Gonai et al, 2004). The sensitivity of lettuce seed germination to inhibition by ABA is enhanced at higher temperatures (Robertson and Berrie, 1977;Roth-Bejerano et al, 1999).…”
mentioning
confidence: 99%